2021
DOI: 10.1002/lary.29618
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Role of Nintedanib in Tracheal Stenosis After a Tracheal Wound

Abstract: Objectives/Hypothesis Tracheal stenosis is an obstructive disease of the upper airway that commonly develops as a result of abnormal wound healing. We evaluated the anti‐inflammatory and antifibrotic properties of nintedanib on tracheal stenosis both in vitro and in vivo. Study Design Prospective controlled animal study and in vitro comparative study of human cells. Methods An animal model of tracheal stenosis was induced via tracheal trauma. Postsurgical rats were orally administered with nintedanib (10 or 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…www.nature.com/scientificreports/ Differentiation of fibroblastic cells into myofibroblasts, which are the major source of ECM components and are considered significant effector cells of tissue fibrosis, is a primary process in the development of tissue fibrosis, and TGF-β induces this process 21 . α-Smooth muscle actin (α-SMA, a marker for a subset of myofibroblasts), FIBRONECTIN (an ECM component), and COL1A1 (a gene that produces a component of type I collagen) are used as markers for fibrosis 21,22 . Western blot analysis confirmed that the protein expression of α-SMA, COL1A1, and FIBRONECTIN was induced in irradiated primary tumors of 4T1-Luc allografted mice, and these increased markers were significantly decreased by co-treatment with vactosertib (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Differentiation of fibroblastic cells into myofibroblasts, which are the major source of ECM components and are considered significant effector cells of tissue fibrosis, is a primary process in the development of tissue fibrosis, and TGF-β induces this process 21 . α-Smooth muscle actin (α-SMA, a marker for a subset of myofibroblasts), FIBRONECTIN (an ECM component), and COL1A1 (a gene that produces a component of type I collagen) are used as markers for fibrosis 21,22 . Western blot analysis confirmed that the protein expression of α-SMA, COL1A1, and FIBRONECTIN was induced in irradiated primary tumors of 4T1-Luc allografted mice, and these increased markers were significantly decreased by co-treatment with vactosertib (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It targets the receptors of VEGF, PDGF and FGF and can interfere with both classic and non-classic TGF-Β1 signalling pathways. In a preclinical rat model, nintedanib proved to effectively prevent tracheal stenosis by inhibiting fibroblast proliferation, migration and differentiation, and by suppressing TGF-Β1/SMAD2/3 and ERK1/2 signalling pathways [ 89 ]. As suggested by preclinical data, there is a rationale for using drugs that specifically block TGF-Β pathway in LTS.…”
Section: Discussionmentioning
confidence: 99%
“…Those benign diseases mainly include iatrogenic complications and trauma. Currently, many studies provide interesting perspectives in treatment strategies in iatrogenic complications after endotracheal intubation or tracheal tube insertion which lead to airway obstruction [8][9][10]. Wagner [11] have demonstrated that the outcome of keloids following burns are different from those developing after mechanical trauma.…”
Section: Discussionmentioning
confidence: 99%